EFFECT OF UTERINE LAVAGE ON BACTERIAL COUNT AND CONCEPTION RATE IN REPEAT BREEDER CROSSBRED COWS - REDDY, N CHANDRA SEKHAR; BRAMHAIAH, K V; NAIDU, K SUBRAMANYAM; BABU, A JAGADEESH; KUMAR, R V SURESH (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out to study the effect of uterine lavage on reduction of uterine infectionand infertility in 24 repeat breeder crossbred cows. After treatment of these cows with either antibiotics or uterinelavage or uterine lavage+antibiotics or control at estrus, the number of bacterial colony counts were not differentsignificantly among the groups but significant within the group. Same has resulted in a conception rate of 66.66,66.66, 83.33 and 16.67%, respectively.
Keywords: Repeat breeder; Uterine lavage; Uterine infection